Visual and Environmental Stimuli Preferences in Pediatric Spaces - Anggra Ayu Rucitra; Purwanita Setijanti; Asri Dinapradipta; Ruka Kosuge (Engineering Proceedings)
Interior design is considered and practiced as a visual discipline in architecture. The environment and buildings are appreciated through visual representations. We explored how sensory interactions shape a genuine multisensory experience with visual stimulation as a primary focus in architecture and interior design. It is important to consider different factors that contribute to visual stimulation when designing spaces. Visual stimulation is experienced differently, depending on the observer, and it is important to understand how children perceive stimuli. Therefore, we determined the visual factors captured by children. The embedded design method was used for qualitative mapping of visual factors and 3D animation creation for visualization. Eye-tracking experiments were conducted to examine the factors that captured the attention of children. Children were attracted to moving objects such as videos, followed by images on walls, playgrounds, windows, and furniture. Fostering positive distraction is important in designing spaces for children.